2017
DOI: 10.1364/josaa.34.000264
|View full text |Cite
|
Sign up to set email alerts
|

Long period fiber gratings with off-resonance spectral response based on mechanical oscillations

Abstract: We present long period fiber gratings with off-resonance spectral response. Our long period fiber gratings are created by the periodic structure of large perturbations in the fiber diameter. These perturbations result in unique spectral response, even in off-resonance frequencies. Writing these long period fiber gratings is based on utilizing the mechanical vibrations of tapered fibers during the tapering process. This writing method is simple and robust; it has high efficiency, high reproducibility, and low p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We start by tapering a fiber down to a 6 µm width over a length of 30-50 mm [28,29]. When a fiber is tapered below 20 µm, the light is no longer guided by the core but by the cladding, which leads to an evanescence field outside the fiber.…”
Section: A Simple Micro-knotmentioning
confidence: 99%
“…We start by tapering a fiber down to a 6 µm width over a length of 30-50 mm [28,29]. When a fiber is tapered below 20 µm, the light is no longer guided by the core but by the cladding, which leads to an evanescence field outside the fiber.…”
Section: A Simple Micro-knotmentioning
confidence: 99%
“…We measured the statistics of ultrafast rogue waves in fiber lasers and found that the underlying mechanism is different than what was previously considered. We will continue to investigate extreme events in different schemes, such as phase locked fiber lasers, 6, 10-13 fiber lasers with unique states of polarization, 14,15 and different types of fiber components [16][17][18][19] We hope to utilize our temporal imaging to focus light through dispersive material and to create rogue waves for high resolution imaging with nano-particles. [20][21][22][23][24][25]…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…This creates coupling between different modes in the cavity. We analyzed that by considering the coupling between different modes, t × , according to [13,21]:…”
mentioning
confidence: 99%